Reconstruction of phylogenetic relationships in a highly reticulate group with deep coalescence and recent speciation (Hieracium, Asteraceae) - Krak, K; Caklová, P; Chrtek, J; Fehrer, J (Heredity, 2013)
Phylogeny reconstruction based on multiple unlinked markers is often hampered by incongruent gene trees, especially in closely related species complexes with high degrees of hybridization and polyploidy. To investigate the particular strengths and limitations of chloroplast DNA (cpDNA), low-copy nuclear and multicopy nuclear markers for elucidating the evolutionary history of such groups, we focus on Hieracium s.str., a predominantly apomictic genus combining the above-mentioned features. Sequences of the trnV-ndhC and trnT-trnL intergenic spacers were combined for phylogenetic analyses of cpDNA. Part of the highly variable gene for squalene synthase (sqs) was applied as a low-copy nuclear marker. Both gene trees were compared with previous results based on the multicopy external transcribed spacer (ETS) of the nuclear ribosomal DNA. The power of the different markers to detect hybridization varied, but they largely agreed on particular hybrid and allopolyploid origins. The same crown groups of species were recognizable in each dataset, but basal relationships were strongly incongruent among cpDNA, sqs and ETS trees. The ETS tree was considered as the best approximation of the species tree. Both cpDNA and sqs trees showed basal polytomies as well as merging or splitting of species groups of non-hybrid taxa. These patterns can be best explained by a rapid diversification of the genus with ancestral polymorphism and incomplete lineage sorting. A hypothetical scenario of Hieracium speciation based on all available (including non-molecular) evidence is depicted. Incorporation of seemingly contradictory information helped to better understand species origins and evolutionary patterns in this notoriously difficult agamic complex.
Keywords: DNA chloroplastová; Genetic Speciation; Asteraceae; Farnesyl-Diphosphate Farnesyltransferase; Crosses, Genetic; fylogeneze; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; molekulární sekvence - údaje; Models, Genetic; Plant Proteins; vznik druhů (genetika); mezerníky ribozomální DNA; genetické markery; křížení genetické; DNA, Chloroplast; farnesyl-difosfofarnesyltransferasa; modely genetické; DNA, Ribosomal Spacer; Molecular Sequence Data; Genetic Markers; rostlinné proteiny